2012
DOI: 10.2147/jmdh.s28240
|View full text |Cite
|
Sign up to set email alerts
|

Volunteering in dementia care – a Norwegian phenomenological study

Abstract: IntroductionThe number of people suffering from dementia will increase dramatically in the future, and this will be a great challenge and concern for health care services. It is assumed that volunteers will strengthen community health care services more in the future than they do today.AimThe aim of this study was to elucidate lived experiences of working as a volunteer in an activity center with adapted activities for home-dwelling people with early stage dementia.MethodsQualitative interviews were implemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 19 publications
6
17
0
Order By: Relevance
“…As dementia develops, the supporters may need contact with professionals to discuss emerging problems and obtain advice. In accordance with other studies [36,37], supporters should be informed and supported while maintaining the informality of the contact with the people with YOD. In this way, the supporter service should be more systematically integrated into the health care system, coordinated, and expanded.…”
Section: Discussionsupporting
confidence: 54%
“…As dementia develops, the supporters may need contact with professionals to discuss emerging problems and obtain advice. In accordance with other studies [36,37], supporters should be informed and supported while maintaining the informality of the contact with the people with YOD. In this way, the supporter service should be more systematically integrated into the health care system, coordinated, and expanded.…”
Section: Discussionsupporting
confidence: 54%
“…Volunteering leads to interactions with other older adults and society, which, as described by Ziegelmann and Knoll [48], can be understood as a distal health behaviour and as a psychosocial pathway to health-related outcomes. Our findings support Söderhamn et al's [49] finding that the context of volunteering for older adults is important for the benefits they experience and for their retention related to be part of a social setting, having an influence on the voluntary work, and the possibility to develop. However, there is a need for a better understanding of these dynamics in daily voluntary work and the generation of positive health benefits from the older adult volunteers' perspective.…”
Section: Discussionsupporting
confidence: 90%
“…In a study by Dale et al,9 the sense of being useful to other people is emphasized, as well as taking care of grandchildren. Being a volunteer was shown to be a major positive experience in a study on volunteering in dementia 42. The participants in that study reported that they performed well and expressed feelings of satisfaction.…”
Section: Discussionmentioning
confidence: 96%